15th International Conference on Dependability and Quality Management ICDQM-2012 (Proceedings review) - Pokorni, Slavko J. (Vojnotehnički glasnik / Military Technical Courier, 2013)
The basic information about overal results, significance, international programme committee and working areas of the 15th International Conferemce on Dependability and Quality Management ICDQM-2012 and 3nd International Conference on Life Cycle Engineering and Management, which was held under the same acronim ICDQM-2012, are given in this paper. This year conference is the second on the number of papers since the begining of the conference. The number and structure of papers, and review of papers presented by participants from Armed forces and Ministry of defense of Republic of Serbia as plenary lectures and in sections: Quality Engineering, Reliability Engineering, Concurent Engineering, Systems Engineering, and Military Engineering are alsou given.